Keputusan Healing Mahasiswa Trend Atau Coping pada Tekanan Akademik - Nursholihah, Aprilia; Nihayah, Intan Sholihul; Sijabat, Rauly (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Academic stress is an increasingly complex problem experienced by many students, especially amidst increasing academic demands, changing learning patterns, and psychological pressures influenced by the development of digital technology. Students are required to adapt to high workloads, rigorous evaluation systems, and the rapid flow of information. If not managed effectively, this can impact mental health, learning motivation, and academic performance. Therefore, adaptive strategies are needed to help students manage academic stress effectively. This study aims to explore the meaning and practice of self-healing as a coping strategy used by students to deal with academic stress and maintain mental well-being. This study used a qualitative approach with a descriptive design. Data were obtained through in-depth interviews with active students experiencing academic stress and who have implemented self-healing practices, both independently and through the influence of digital media. Informants were selected using a purposive sampling technique, while data analysis employed the Miles and Huberman interactive analysis model, which includes continuous data reduction, data presentation, and conclusion drawing. The research results indicate that students’ academic stress is primarily caused by difficulties adapting to the academic environment, the high burden of coursework, pressure to achieve academic achievement, and limitations in understanding learning materials. Students define self-healing as a conscious effort to calm themselves, manage their emotions, and restore their mental state so they can return to optimal academic activities. Self-healing practices include self-reflection, religious activities, journaling, spending time outdoors, consuming digital entertainment, and fostering social interactions with loved ones. Social media serves as a source of information, references, and inspiration for self-healing practices, while also shaping it as a popular phenomenon among students.